2022
DOI: 10.30604/jika.v7is1.1202
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Nurse Time Management with Documentation of Nursing Care in The Inpatient Room of Muhammadiyah Hospital in Metro

Abstract: Nursing documentation is necessary in the nursing care process. In Indonesia, nursing care documentation is still not up to standard, leading in issues with nursing care implementation, such as poor documentation of quality of care provided in hospitals, making it difficult to verify that nursing care was administered correctly. Documentation of nursing care is an indicator of nurse performance which is influenced by nurse time management. The research objective was to determine the correlation between nurse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…The study aimed to determine the relationship between time management, professional self-e cacy, and the quality of nursing care among nurses in Western Iran. The participants reported moderate levels of time management (80.3%), which is consistent with the ndings of studies conducted by Yunitasari et al (2022), Hashemizadeh et al (2013) and Heydari et al(2012) [32,39,40]. In contrast, a study by Barua et al (2019) in Bangladesh reported poor time management among nurses, which differs from the current study's ndings [41].…”
Section: Discussionsupporting
confidence: 89%
“…The study aimed to determine the relationship between time management, professional self-e cacy, and the quality of nursing care among nurses in Western Iran. The participants reported moderate levels of time management (80.3%), which is consistent with the ndings of studies conducted by Yunitasari et al (2022), Hashemizadeh et al (2013) and Heydari et al(2012) [32,39,40]. In contrast, a study by Barua et al (2019) in Bangladesh reported poor time management among nurses, which differs from the current study's ndings [41].…”
Section: Discussionsupporting
confidence: 89%
“…Results resonate with other research, showing that mental workload positively correlated with performance in health service [9], [10], business [11], education [12], [13]. However, contrasting findings from Ref.…”
Section: Discussionsupporting
confidence: 82%